2017
DOI: 10.1101/223099
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fe2+/H2O2-mediated oxidation of homogentisic acid indicates the production of ochronotic and non-ochronotic pigments. Implications in Alkaptonuria and beyond

Abstract: Homogentisic acid (HGA) can be oxidized by a combination of Fe 2+ and H 2 O 2 into a darkly colored high molecular mass pigment. Increasing the concentration of H 2 O 2 can lead to the formation of a high molecular mass material that exhibits less absorbance in the visible range of the electromagnetic spectrum, while maintaining a strong absorbance in the UV range of the electromagnetic spectrum. FT-IR spectroscopy did indicate the presence of a chemical feature in the pigments generated through H 2 O 2 -medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(56 citation statements)
references
References 26 publications
6
50
0
Order By: Relevance
“…27,43 However, these reports involve the treatment of pre-formed MNs with H 2 O 2 , while our work focuses on the use of H 2 O 2 in the synthesis of MNs. In this and our previous reports [14][15][16] we confirmed that the presence of high concentrations of H 2 O 2 does lead to MN-like materials with decreased colored appearance and enhanced fluorescence emission. These physicchemically different MN-like pigments do not appear to undergo any depolymerization as the SEC retention times of all the MN-like materials are very similar; independent of the reaction conditions that generated the pigments.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…27,43 However, these reports involve the treatment of pre-formed MNs with H 2 O 2 , while our work focuses on the use of H 2 O 2 in the synthesis of MNs. In this and our previous reports [14][15][16] we confirmed that the presence of high concentrations of H 2 O 2 does lead to MN-like materials with decreased colored appearance and enhanced fluorescence emission. These physicchemically different MN-like pigments do not appear to undergo any depolymerization as the SEC retention times of all the MN-like materials are very similar; independent of the reaction conditions that generated the pigments.…”
Section: Discussionsupporting
confidence: 89%
“…However, it is worth pointing out that for greying of hair or vitiligo, conditions that are associated with the loss of pigmentation, the presence of increased levels of H 2 O 2 has been discussed as a potential contributing factor to these changes in pigmentation. [44][45][46] Our current and previous observations [14][15][16] do suggest a hypothesis that the absence of dark colors may not necessarily mean the absence of MN-like molecules, but could mean the presence of a different type of MN-like material. It is worth pointing out that the light-colored MN-like materials generated in the presence of high concentrations of H 2 O 2 do absorb or scatter light in the UV range of the electromagnetic spectrum, although to a less efficient extent than the dark-colored materials.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations